2002
DOI: 10.1029/2001gc000155
|View full text |Cite
|
Sign up to set email alerts
|

Structure of uppermost fast‐spread oceanic crust exposed at the Hess Deep Rift: Implications for subaxial processes at the East Pacific Rise

Abstract: The uppermost 2 km of the oceanic crust created at the fast spreading (135 mm yr À1 , full rate) equatorial East Pacific Rise (EPR) is exposed for tens of kilometers along escarpments bounding the Hess Deep Rift. Mosaics of large-scale digital images from the remotely operated vehicle (ROV) Argo II and direct observations from the submersible Alvin document a degree of geological complexity and variability that is not evident from most studies of ophiolites or prevailing models of seafloor spreading. Dramatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
178
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(185 citation statements)
references
References 95 publications
6
178
1
Order By: Relevance
“…Barring passive rotation, however, they were likely not part of the fault system inferred from seafloor scarps [Bohnenstiehl and Carbotte, 2001] and modeled as a response to flexural forces during seafloor spreading [Buck et al, 2005;Behn and Ito, 2008;Ito and Behn, 2008]. Instead, the faults were part of a set that is driven primarily by magmatic accretionary processes [Karson et al, 2002a;Carbotte et al, 2003] and, as suggested here, varying pressure conditions due to the influence of hydrothermal fluid flow on fault mechanics.…”
Section: An Evaluation Of Axial Versus Axial Flank and Off-axis Faultmentioning
confidence: 99%
See 1 more Smart Citation
“…Barring passive rotation, however, they were likely not part of the fault system inferred from seafloor scarps [Bohnenstiehl and Carbotte, 2001] and modeled as a response to flexural forces during seafloor spreading [Buck et al, 2005;Behn and Ito, 2008;Ito and Behn, 2008]. Instead, the faults were part of a set that is driven primarily by magmatic accretionary processes [Karson et al, 2002a;Carbotte et al, 2003] and, as suggested here, varying pressure conditions due to the influence of hydrothermal fluid flow on fault mechanics.…”
Section: An Evaluation Of Axial Versus Axial Flank and Off-axis Faultmentioning
confidence: 99%
“…[3] There are two methods of accessing subsurface ocean crust: deep crustal drilling [Alt et al, 1996;Wilson et al, 2006] and submersible investigations of tectonic escarpments, also known as ''tectonic windows'' [Karson, 2002;Karson et al, 2002aKarson et al, , 2002bPockalny et al, 2004]. The most recently investigated Pacific-crust tectonic window is the Pito Deep Rift (PDR), where in situ ocean crust generated at the SEPR is exposed along escarpments with kilometer-scale relief (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Results of Expedition 309/312 will determine the thicknesses of these upper crustal units at Site 1256 as well as document the styles of deformation and magmatic accretion. Although studies of tectonic exposures of oceanic crust suggest that intense brittle deformation, faulting and localized zones of fracturing, and large amounts of dike rotation are common within sheeted dike complexes in crust formed at fast and intermediate spreading rates (Karson, 2002;Karson et al, 2002;Stewart et al, 2005), it is difficult to separate primary mid-ocean-ridge geometries from deformation related to the exposure in these tectonic windows. In contrast, large blocks of the sheeted dike complexes in the Semail ophiolite in Oman exhibit little of such faulting and distributed fracturing (Umino et al, 2003).…”
Section: Scientific Objectives Of Expeditions 309 and 312mentioning
confidence: 99%
“…Fourteen dives conducted during two Alvin dive programs (1990, 1999) investigated a 4-km-wide area which records -60,000 years of spreading history, with units younging from west to east (Figure 2a). Volcanic rocks form the crest of the horst and grade downslope (to ,the south) into the sheeted dike complex, followed by the uppermost plutonic sequence (see inset in Figure 2a for cross section) [Karson et al, 1992;2001]. In this 4-km-wide area, the thickness of the volcanic sequence increases (from <200 to >600 m) and the depth of the volcanic-sheeted dike transition deepens (from-2000 to 2500 m below sealevel (bsl)) from west to east.…”
Section: Tectonic Setting and Geological Relationshipsmentioning
confidence: 99%
“…However, on the basis of studies from other areas [see Macdonald, 1998], it is conceivable that magma supply was not constant during the construction of the crust exposed at the rift shoulder horst. In Figure 8 we show a schematic cross section of a fast spreading ridge [Karson et al, 2001] that identifies the relative positions of areas 1 and 2 such that area 1 is under construction at the axis while area 2 is located 2-3 km off-axis. We speculate that area 1 was constructed during a period of high magma supply and that at some stage during its construction, hydrological and thermal conditions caused discharge to be focused in the shallow dikes for tens to a few hundreds of years (i.e., life cycle of EPR vent sites).…”
Section: Link With Spreading Axismentioning
confidence: 99%